Student perceptions of learning management at the Faculty of Accounting and Administration at UACH - Armendáriz Vega, Jorge; De la Rosa Flores, Carlos Cristian; Chávez Hernández, Paul Adrián (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To analyze students’ perceptions from the Faculty of Accounting and Administration at Universidad Autónoma de Chihuaha [UACH] regarding the management of learning delivery. MATERIAL AND METHOD: A descriptive and cross-sectional research study was conducted in 2024, based on a mixed approach with a hypothetical-deductive method. To collect data, a survey was administered to 148 students, designed to investigate demographic aspects, as well as perceptions regarding educational administration, teaching staff, infrastructure, and resources. The sample was calculated with a confidence level of 86% and a margin of error of 6%. RESULTS: 54.1% of students rated the educational administration as “good”, while 64.9% considered the administrative staff accessible. Regarding the teaching staff, 48.6% rated them as “good”, and 54.7% perceived them as “available” outside the lesson hours. The infrastructure was rated as “good” by 45.9%, and the technological facilities as “adequate” by 43.2%. CONCLUSIONS: Student perception reflects general satisfaction with educational administration, although areas for improvement remain, especially in administrative accessibility and technological resources.